Development and evaluation of the interactive English Language Literacy System (i-ELLS) for online reading comprehension - Noorizah Mohd Noor,; Hazita Azman,; Nor Fariza Mohd Nor,; Afendi Hamat,; Nadzrah Abu Bakar, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
i-ELLS (interactive English Language Literacy System) is a prototype that is developed based on empirical evidence of online literacy processes and reading strategies used by multilingual Malaysian readers reading for academic purposes. Based on these findings, several technological features such as discussion tools, real-time audio-visual chat, personal knowledge construction and annotation tools were developed for the prototype in order for the system to cater to the reading strategies identified. The i-ELLS prototype presents a novel way for readers to interact with online textual materials that can be personalized and interacted with in order to assist with literacy and comprehension. It is also designed for collaborative activities in order to maximize the benefits of online environments. It is currently being used in a postgraduate teaching and learning context at Universiti Kebangsaan Malaysia. This paper reports on the development as well as the students’ overall evaluation on the use of the system. The feedback on the use of i-ELLS revealed positive and negative responses. These findings are important as they provide valuable insights on how students read online as well as the technology needed to support an online academic reading environment.